PERAN PELAKSANA PENYULUHAN HUKUM KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM BANTEN DALAM SOSIALISASI BANTUAN HUKUM GRATIS BAGI MASYARAKAT TIDAK MAMPU - Anton Aulawi; Ratu Mimi Darniasih (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
The purpose of this research was to determine the role of Legal Counselors in the Regional Office of the Banten Ministry of Law and Human Rights in the socialization of free legal aid for the poor. In this research the authors use a methodology with a qualitative approach. In the research to be conducted, researchers will use three data collection techniques, by interview, observation, and documentation. The results of this research are that legal aid regulated by Rule Number 16 of 2011 years concerning Legal Aid, is the state's obligation to provide the rights of every citizen to get legal protection and human rights, especially for the poor. The provision of legal aid as a state obligation to implement the constitutional rights of the poor is to provide funding to legal aid organizations with the State Budget. The state is present to provide legal assistance, one of which is by means of the Regional Office of the Ministry of Law and Human Rights Banten. The method of socialization about free legal assistance to the poor is done by legal counseling activities with direct and indirect methods; firstly, legal counseling is carried out solely by law enforcement officers from the Regional Office of the Ministry of Law and Human Rights Banten. Secondly, legal counseling is carried out by accredited legal aid organizations but with budgets derived from legal aid funds from the state with the authority of budget users from the Ministry of Law and Human Rights.